Structure-acidity-coking correlation in TEAOH-modified hierarchical ZSM-5 for phenol catalysis: Experimental investigation and GCMC/MD simulation - Qingzhou Zeng; Yichao Zhang; Xuefeng Han; Xianghui Liu; Hongyu Zhao; Ming Zeng; Zhijun Ma; Shucheng Liu (Fuel, 2026)

Microplastics stimulating polycyclic aromatic hydrocarbon biodegradation via cometabolism in historically coking-contaminated soil: Superior performance of biodegradable microplastics - Guixiang Zhang; Hongyu Zhang; Fengsong Zhang; Lanfang Han; Ke Sun; Hao Wu; Chen Liang; Dandan Liu; Long Ping; Baoshan Xing (Environmental Pollution, 2026)

An appearance-independent multi-object tracking framework for group-housed pigs - Liwen Chen; Lu Yang; Jianzhai Wu; Xiangfang Tang; Guodong Cheng; Hongyu Zhang; Jianyu Fang; Chao Ma; Shuqing Han (Computers and Electronics in Agriculture, 2026)

Development of low-ammonia MICP technology based on Mg2 +-enhanced nitrogen assimilation and biomineralization - Linlin Zhang; Yue Zhao; Hongyu Han; Ruoxi Li; Zhaofeng Liu; Yuqing Li; Shenghui Yang; Wen Nie (Journal of Environmental Chemical Engineering, 2026)

Evolutionary patterns of chemical-pore structure in low-rank coal under acid-based CO2 foam fracturing fluid pressure - Hongyu Pan; Hongjiao Chen; Bingnan Ji; Mingyue Pan; Siyu Chen; Mingrui Han; Hongli Chen (Fuel, 2026)

Trophic dynamics of parrotfish in a degraded coral reef ecosystem in the Xisha Islands, South China sea - Jinfa Zhao; Teng Wang; Yu Liu; Hong Li; Huaxue Liu; Hongyu Xie; Jianzhong Shen; Yayuan Xiao; Xuefu Ao; Hai Huang; Yong Liu; Qiuying Han (Environmental Research, 2026)

Dual-responsive hydrogel coils with shape memory effect for enhanced aneurysm embolization - Min Ye; Ming Qiu; Yunpeng Cai; Nanxiang Li; Jianguo Han; Yan Zhou; Yue Xi; Hongyu Zhao; Yujie Liao; Xinpeng Niu; Long Han; Qingsong Xu; et al. (Chemical Engineering Journal, 2026)

Deep learning-driven semantic change detection in remote sensing: a systematic review - Jing Wang; Cui Ni; Peng Wang; Hongyu Li; Shoumao Guo; Qingxu Han; Zhongzheng Zhen (International Journal of Remote Sensing, 2026)

Vibration transmission and ballast particle dynamic response of shoulder-type sleeper under larger axle load - Zhongxia Qian; Hong Xiao; Shaolei Wei; Yuefeng Han; Hongyu Que; Wenbo Zheng (Transportation Geotechnics, 2026)

Retraction notice to “Determining the spatial non-stationarity underlying social and natural environment in thyroid cancer in China” [Sci. Total Environ. 870 (2023) 162009] - Xiyu Zhang; Yongqiang Lai; Xiaodan Bai; Bing Wu; Wenjing Xiang; Chenxi Zhang; Guihong Geng; Wenqing Miao; Qi Xia; Qunhong Wu; Huiying Yang; Yanjie Wang; et al. (Science of The Total Environment, 2026)

Nanosecond-laser-printed LiTFSI-enabled ionic hydrogels for wearable sensing and gel-electrolyte applications - Lei Chen; Renbao Wang; Yuhan Liu; Chen Hu; Tong Zang; Haorui Lv; Dongfeng Qi; Xiang Han; Meng Shi; Qingxuan Sui; Hongyu Zheng (Chemical Engineering Journal, 2026)

ZNF200 and DDX17 regulatory loop promotes tumor growth and metastasis by activating RBPJ transcription in non-small cell lung cancer - Yanke Zhang; Hongbin Zhu; Xueqin Wang; Wei Dong; Maoyu Zhang; Xinyue Song; Danye Han; Qian Chai; Xueyi Feng; Xiaozheng Wei; Hongyu Chen; Yonghuai Li; et al. (Science China Life Sciences, 2026)

Experimental investigation of nonlinear hydrodynamic properties of the T-foil on a high-speed trimaran - Shijie Liu; Lincen Han; Hongyu Lin; Shaoqing Liu; Xi Chen; Yichen Jiang (Ocean Engineering, 2026)

Long-term HRV metrics may assist in differentiating between prolonged disorders of consciousness and emergence from minimally conscious state : a cross-sectional study - Xinwei Tang; Na Ren; Zuojun Cao; Zi Yu; Xu Han; Weiqiang Cai; Youbei Yang; Lisi Lu; Mukedaisihan Maisedi; Zuowen Sun; Junfa Wu; Yi Wu; et al. (Acta Neurologica Belgica, 2026)

Phosphoglycerate mutase 1 is implicated in maduramycin resistance and host cell invasion in Eimeria tenella - Jiayu Bai; Qiping Zhao; Ke Xiao; Liujia Li; Shunhai Zhu; Hui Dong; Wenqi Han; Yu Yu; Jinwen Wang; Qiaoyun Ren; Hongyu Han (Veterinary Parasitology, 2026)

Genetic diversity analysis of three geographical populations of Triplophysa yarkandensis macroptera in arid northwestern China - Ya Liu; Hangyu Lin; Hongyu Ke; Han Zhao; Zhongmeng Zhao; Shengqi Su; Qiang Li (Journal of Arid Environments, 2026)

Luteolin-stabilized pickering emulsion for encapsulating Enterococcus hirae: preparation, characterization, and synergistic effects on hyperuricemia - Chengtao Han; Songhao Che; Hui-Min Li; Yan-Yu Chi; Jun-Yan Xiang; Qiuhong Xie; Hongyu Xiang (Food Research International, 2026)

Self-folded three-dimensional RNA origami: Directly sprayable RNAi biopesticide for lepidopteran pest control - Bailu Pang; Hongyu Han; Jiaxin Zhang; Yongan Tan; Yiping Jiang; Zhiping Xu; Yufang Xu; Weiping Zhu; Yangyang Yang; Xuhong Qian (Chemical Engineering Journal, 2026)

Gap-filled spatiotemporal reconstruction of XCH4 data and analysis of methane emission patterns - Qian Xiao; Yong Wan; Ge Han; Yu Liu; Yuhang Liu; Xiaowen Li; Hongyu Zhou (Atmospheric Pollution Research, 2026)

Holistic evolution of the Bohai Sea complex system: Insights from interacting drivers - Han Huang; Tao Zou; Teng Liu; Hongyu Wang; Zhixuan Wang; Ningning Tao; Yanfang Li; Hao Fan; Fei Xie; Weidong Zhai; Guizhi Wang; Yongwen Zhang; et al. (Marine Environmental Research, 2026)

Antimicrobial mechanism of green citrus peel extract against Gluconobacter cerinus causing decay in ‘Xuxiang’ kiwifruit - Juan Xie; Giri Raj Tripathi; Zhangxing Li; Hongyu Li; Xiaobo Liang; Peng Han; Ge Zhao; Miaomiao Yang (International Journal of Food Microbiology, 2026)

Trade-off-free intrinsically stretchable electroluminescent films enabled by a thermally activated delayed fluorescence plasticizer - Wenzhong Bian; Xinxin Ban; Junyi Chen; Mengting Li; Caixia Yang; Hongyu Zhuang; Shuang Chen; Jiangqi Jiang; Wenli Shi; Hai Zhou; Youqiang Qian; Zhaoxiang Han; et al. (Chemical Engineering Journal, 2026)

Exploring the high-concentration powdered carrier bio-fluidized bed process nitrogen removal performance: Effect of dissolved oxygen - Yingxue Cui; Zixuan Liang; Hongyu Yu; Donghai Yang; Dianhai Yang; Hongbo Han; Xiaohu Dai (Journal of Environmental Sciences, 2026)

Melatonin alleviates cholestatic liver injury through modulating gut microbiota and activating the NRF2/HO-1 antioxidant pathway - Shijing Dong; Jiangpeng Liu; Chenyang Xuan; Simin Zhou; Zongze Han; Chenhui Zhu; Nian Chen; Ruiyun Liu; Weirong Wang; Hongyu Chu; Xue Zhang; Hui Yang; et al. (Tissue and Cell, 2026)

Structural basis for polyphenol-mediated glycemic control: comparative study on catechin oligomerization and gallic acid degradation in simulated gastrointestinal conditions - Yang Liu; Gexin Liu; Yingbo Zhao; Hongyu Li; Luye Yang; Fuliang Han (Food Chemistry, 2026)

Molecular characterization and analysis of enoyl-CoA hydratase/isomerase family protein of Eimeria tenella - Shisi Zhang; Shunhai Zhu; Wenhao Huang; Qiping Zhao; Lu Wang; Hui Dong; Jenwen Wang; Yu Yu; Hongyu Han (European Journal of Protistology, 2026)

Seasonal transmission characteristics, interconnections and risk assessment of bioaerosol-mediated ARGs and bacteria in the underground wastewater treatment plant - Jingyun Ge; Hongyu Tian; Jianwei Liu; Jianbin Sun; Yunping Han (Environmental Research, 2026)

Temporal stability of otolith shape in fishes and its relationship with diet: A case study of parrotfish in Xisha Islands, China - Zhipeng Kang; Yong Liu; Teng Wang; Chunhou Li; Hongyu Xie; Jinfa Zhao; Jianzhong Shen; Hai Huang; Yu Liu; Qiuying Han; Yanqiao Wang (Fisheries Research, 2025)

Mechanical behavior of surface conductors induced by drill string vibrations during deepwater drilling - Qishuai Yin; Jingxuan Tang; Zengcheng Han; Yao Zhou; Hongyu Wan; Yongqi Ma (Ocean Engineering, 2025)

Experimental and numerical study on the ultimate strength of the CFRP hat-stiffened plate under the longitudinal compression - Hongyang Ma; Aijing Han; Hongyu Zhou; Lingge Zhang; Hui Li; Guoqing Feng; Shili Sun (Ocean Engineering, 2025)

Vertical thermal responses of young adults in campus rooftop spaces during winter in the severe cold regions of China - Bo Wang; Wenlong Zhang; Yutong Guo; Guoqiang Ai; Hongyu Zhao; Wanqi Tao; Bingbing Han (Journal of Thermal Biology, 2025)

Integrated evaluation of VOCs pollution from a refuse transfer station: From source emissions to ambient exposure - Hongyu Gong; Shuwen Han; Yifan Zhuo; Xinwei Li; Junyao Zhang; Meng Wang; Shuncheng Lee (Journal of Hazardous Materials, 2025)

Rigid dextrin-based polyurethane foam for sustainable, high-performance building applications - Hongyu Feng; Yudong Hu; Jiangbo Wang; Heyu Chen; Shaohua Jiang; Xiaoshuai Han (Journal of Cleaner Production, 2025)

Modulation of flavour perception under sodium-reduced conditions: A sensory–metabolic interaction framework driven by Debaryomyces hansenii SH4 and KCl - Han Li; Hongyu Li; Qianqian Yu; Chengfeng Sun; Huaishu Wang; Yonglin Gao; Rongxin Wen (Food Research International, 2025)

Waste wood in agroforestry systems improves phallus dongsun yield by regulating soil bacterial interactions and improving soil properties - Wei Ge; Yang Gui; Guosheng Zhu; Wanbing Huang; Biao Li; Hongyu Liu; Yingying Lu; Qingcheng Liu; Chunbo Dong; Yanfeng Han (Applied Soil Ecology, 2025)

Identification of Ermiao Fang Jiawei extract as potential synergist against fluconazole-resistant Candida albicans in vitro and in a vulvovaginal candidiasis model - Jinyun Song; Xuxi Cheng; Jinghan Gao; Zihao Liang; Han Xue; Hongyu Zhao (Natural Product Research, 2025)

Adaptive resistance and defense evolution in microplastics-mediated biological exposure interfaces in municipal wastewater treatment systems - Hongyu Tian; Jianwei Liu; Yunping Han; Shouliang Yi (Journal of Hazardous Materials, 2025)

Directed producing singlet oxygen for tetracycline hydrochloride degradation using red mud-based heterojunction within sonophotocatalysis system - Yi Han; Mengxin Guo; Hongcheng Gao; Changyong Zhang; Keping Lu; Dejin Wang; Hongyu Xia; Zheng Peng (Environmental Research, 2025)

Plant-driven circular strategy: combined remediation of Cr(VI)-contaminated soil with leaves extracts and Biomass@nZVI/BC from leaves residues - Hongyu Liu; Jing Ren; Qingyun Han; Huan Zhang; Huicai Wang; Junfu Wei (Chemical Engineering Journal, 2025)

Energy burden and asthma prevalence in U.S. cities: An emerging social determinant of health - Soojin Han; Tina Hartert; Junfeng (Jim) Zhang; Wei-Chung Su; Pingsheng Wu; Youqin Huang; Qian Lu; Hongyu Wang; Hua Zhao; Yanfang Su; Ming Hu; Kai Zhang (Science of The Total Environment, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Airborne human-associated ARGs in municipal wastewater treatment plants - Ying Wang; Yunping Han; Lin Li; Jianwei Liu; Hongyu Tian (Journal of Hazardous Materials, 2025)

Constructing halogen-functionalization magnetic covalent organic frameworks for enhancing the endocrine disruptors adsorption capacity - Haijuan Jiang; Han Tao; Shaoxiang Yang; Hongyu Tian; Baoguo Sun (Food Chemistry, 2025)

Alkali/alkaline earth metals doped holey penta-hexagonal graphene for ultrahigh-performance CO2 capture and separation over N2/CH4 - Tiantian Qiao; Hongyu Pan; Ziyi Han; Zishuo Zhang; Sainan Zhou; Xiaoqing Lu; Yongqing Li (Fuel, 2025)

Novel ductile and durable engineered cementitious composite columns reinforced with steel-FRP composite bars: Axial compression behavior and design - Yulei Bai; Qipeng Ma; Shiwen Han; Lin Yang; Yufeng Zhang; Hongyu Zhang (Engineering Structures, 2025)

Introgression of quantitative trait locus qSFWI6D from Aegilops tauschii improves salt tolerance in wheat at seedling stage - Jinhao Han; Hongyu Ren; Mengjia Sun; Mingxuan Li; Cunyao Bo; Jiachuang Fang; Hongwei Wang; Yunlong Pang; Xiaoqian Wang (Theoretical and Applied Genetics, 2025)

Identification of fruitless1 isoforms and their molecular function in gonadal development and courtship in the mud crab Scylla paramamosain - Mengqian Zhang; Yongcheng Xue; Bixun Qiu; Shihao Shi; Xiyi Zhou; Yixi Chen; Hai Liu; Wenfeng Han; Shaharior Hossen; Hongyu Ma (Aquaculture, 2025)

eDNA Metabarcoding Reveals the Depth-Structured Variation of Coral Reef Fish - Jinfa Zhao; Lin Lin; Yong Liu; Teng Wang; Yu Liu; Yayuan Xiao; Jianzhong Shen; Hongyu Xie; Hai Huang; Qiuying Han (Fishes, 2025)
Global coral reef ecosystems face various levels of disturbance pressure. Understanding the depth-structured variation in coral reef fish communities can help us to better grasp and predict the adaptive changes of the ecosystem under different stressors. This study applied eDNA metabarcoding technology to analyze the spatial distribution of the coral reef fish at various depths (0 m, 5 m, 10 m, 15 m, 20 m, 30 m, 40 m, 50 m, and 60 m) within the Xisha Islands of China. The results indicated that the eDNA technology detected a total of 213 amplicon sequence variants (ASVs), including 33 species that were not identified using traditional methods. Herbivorous fish generally dominated in relative abundance across different depths. Moreover, the similarity among depth groups was largely absent, and significant differences existed in fish assemblages across depth gradients, consistent with the unique depth preferences of fish microhabitats. Importantly, our findings revealed distinct depth-structured variation among different functional groups of coral reef fish. Large carnivorous fish initially increased and then decreased along the depth gradient from 0 to 60 m, with a turning point around 20 m, while large herbivorous fish displayed the opposite trend. Small carnivorous and small herbivorous fish consistently declined along the same depth gradient. Additionally, the Margalef index (D) and Function richness (FRic) both displayed a consistent downward trend with increasing depth, while the Shannon–Wiener index (H′), Pielou index (J′), Quadratic entropy (RaoQ), Functional dispersion (FDis), and Functional evenness (FEve) initially increased and then decreased, peaking around 20 m. This study revealed that eDNA metabarcoding is an effective tool for evaluating coral reef fish biodiversity, community composition, and spatial distribution. It enhances our understanding of distribution dynamics and offers valuable insights for coral reef conservation and restoration efforts.

Benefits evaluation of reclaimed water utilization based on the United Nations sustainable development goals - Zhen Liu; Wen Shi; Jiaxuan Gao; Meixuan Zhu; Zhi Su; Yikun Xu; Hongyu Ma; Han Wang; Xiaowen Ding (Process Safety and Environmental Protection, 2025)

Effect of CO2 foam fracturing fluid acidification on pore structure of anthracite and bituminous coal - Hongyu Pan; Hongjiao Chen; Mingyue Pan; Bingnan Ji; Siyu Chen; Mingrui Han; Yan Cao; Xinshuang Cao (Fuel, 2025)

Integration of microbiomics and metabolomics reveals energy metabolism imbalance in crucian carp (Carassius auratus) under saline-alkaline exposure - Lin Han; Wenzhi Liu; Fangying Yuan; Qianwen Liu; Hongyu Cheng; Xiaofeng Jin; Yanchun Sun (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Mechanism of blocking the glutamate pathway to exacerbate oxidative stress, ammonia toxicity and metabolic disorders in crucian carp (Carassius auratus) under saline-alkaline exposure - Wenzhi Liu; Lin Han; Fangying Yuan; Qianwen Liu; Hongyu Cheng; Xiaofeng Jin; Yanchun Sun (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Application of extreme gradient boosting for predicting standard penetration test N-values from cone penetration test data - Xiao Han; Jiangtao Yi; Xiaobin Li; Siyu Li; Hongyu Tang; Zhen Wang; Jingnian Ran (Bulletin of Engineering Geology and the Environment, 2025)

Effective assessment of mixed strains against Fusarium oxysporum f. sp. lycopersici causing tomato wilt - Zhe Han; Shengyi Wang; Ao Gao; Meiqi Dong; Yufeng Xiao; Hongyu Pan; Lining Zheng; Hao Zhang (Physiological and Molecular Plant Pathology, 2025)

MOFs-derived magnetic CoFe bimetallic alloys catalyst radical and non-radical peroxydisulfate activation for efficient rapid organic dye degradation - Hongcheng Gao; Chenyu Huang; Yi Han; Dejin Wang; Weihao Tao; Baoliang Li; Hongyu Xia; Fasong Li; Zhibing Xu; Yi Wang (Journal of Water Process Engineering, 2025)

Recent advancements in the extraction and analysis of phthalate acid esters in food samples - Qian Yang; Yangqing Wu; Shuaihua Zhang; Hongyu Xie; Dandan Han; Hongyuan Yan (Food Chemistry, 2025)

Regularization by double complementary priors for full waveform inversion - Hongyu Qi; Zhenwu Fu; Yang Li; Bo Han; Longsuo Li (Computers & Geosciences, 2025)

Preparation of a novel organic-inorganic composite sludge bioflocculant (SBF) from dewatered sludge as raw material: Characteristics, flocculation mechanism and application for domestic sewage - Jingyun Ge; Hongyu Tian; Lin Li; Yunping Han; Jianwei Liu (Bioresource Technology, 2025)

Phenolic acids alleviated consecutive replant problems in lily by regulating its allelopathy on rhizosphere microorganism under chemical fertiliser reduction with microbial agents in conjunction with organic fertiliser application - Jia Han; Yuanpeng Li; Hui Li; Hongyu Yang; Shilei Luo; Huali Man; Guiying Shi (Applied Soil Ecology, 2025)

Monoclonal antibody development and antigenic epitope identification of infectious bursal disease virus VP5 - Jinze Han; Xinxin Niu; Chengfei Ge; Ziwen Wu; Guodong Wang; Mengmeng Huang; Yulong Zhang; Runhang Liu; Mengmeng Xu; Hangbo Yu; Jingzhe Han; Suyan Wang; et al. (The Veterinary Journal, 2024)

Impact of joint dispatch of reservoir group on water pollution incident in drinking water source area - Zhen Liu; Han Wang; Jiaxuan Gao; Meixuan Zhu; Hongyu Ma; Zhi Su; Xiaowen Ding (Water Research, 2024)

Optimal scheduling study of cascade hydropower stations to ensure ecological flow requirements—A case study of the Gorge Section of the Yongding River, China - Zhen Liu; Zexian Zhang; Hongyu Ma; Jiaxuan Gao; Zhi Su; Han Wang; Gongchen Li; Xiaowen Ding (Science of The Total Environment, 2024)

Metabolic engineering of Escherichia coli for de novo production of 5-hydroxyvalerate via L-lysine α-oxidase pathway - Guodong Wang; Yuanwei Wang; Yingshuai Wu; Shitong Dong; Han Zhao; Hongyu Deng; Yonghua Chen; Wenzhu Song; Ruiming Wang; Chunling Ma (Bioresource Technology, 2024)

An integrated analysis of transcriptome and metabolome to reveal the effects of temperature stress on energy metabolism and physiological responses in Schizothorax wangchiachii muscles - Han Zhao; Zhongmeng Zhao; Can Liu; Jian Zhou; Zhipeng Huang; Yuanliang Duan; Lu Zhang; Hongyu Ke; Jun Du; Chengyan Mou; Qiang Li (Aquaculture, 2024)

Research on mine water source classifications based on BO-CatBoost - Han Li; Zhenwei Yang; Hang Lv; Man Wang; Bo Zhang; Hengrui Yan; Hongyu Zhang (Environmental Monitoring and Assessment, 2024)

Effects of neonicotinoid residues on non-target soil animals: A case study of meta-analysis - Yuxuan Cao; Wenting Zhao; Jinrui Zhang; Daniel M. Figueiredo; Mingyu Zhao; Siyang Ren; Hongyu Mu; Yiyi Li; Huan Lu; Haoyuan Shi; Xin Li; Jindong Li; et al. (Journal of Hazardous Materials, 2024)

Loop PDE of viral capsid protein is involved in immune escape of the emerging novel variant infectious bursal disease virus - Guodong Wang; Nan Jiang; Hangbo Yu; Xinxin Niu; Mengmeng Huang; Yulong Zhang; Wenying Zhang; Jinze Han; Mengmeng Xu; Runhang Liu; Ziwen Wu; Jingzhe Han; et al. (Veterinary Microbiology, 2024)

Large-scale soil application of hydrochar: Reducing its polycyclic aromatic hydrocarbon content and toxicity by heating - Hongyu Si; Rui Wang; Yuqing Zhao; Han Hao; Changkai Zhao; Sen Xing; Hewei Yu; Xiaohui Liang; JiKai Lu; Xiuxiu Chen; Bing Wang (Journal of Hazardous Materials, 2024)

Molecular characterization and functional analysis of Eimeria tenella ankyrin repeat-containing protein - Huilin Guo; Qiping Zhao; Haixia Wang; Shunhai Zhu; Hui Dong; Xinrui Xie; Lihui Wang; Lang Chen; Hongyu Han (European Journal of Protistology, 2024)

Lightweight, ultra-broadband SiOC-based triply periodic minimal surface meta-structures for electromagnetic absorption - Junbin Lu; Mingming Sheng; Hongyu Gong; Jie Jing; Xiaobin Zhou; Jianqiang Bi; Weibin Zhang; Guifang Han; Zidong Zhang; Haoyu Fang; Yijie Zhou; Ke Bi (Chemical Engineering Journal, 2024)

Transcriptomic analysis and knockout experiments reveal the role of suhB in the biocontrol effects of Pantoea jilinensis D25 on Botrytis cinerea - Lining Zheng; Zhe Han; Shengyi Wang; Ao Gao; Ling Liu; Hongyu Pan; Hao Zhang (Science of The Total Environment, 2024)

Exploring the characteristics and drivers of virtual cropland trade of major agricultural products in China - Han Meng; Liwei Xing; Jiaxuan Hu; Chen Shen; Hongyu Zhang; Jianzhai Wu (Journal of Cleaner Production, 2024)

Hydrogeochemical and isotopic evidences of the underlying produced water intrusion into shallow groundwater in an oil production area, Northwest China - Hongyu Zhang; Xu Han; Guangcai Wang; Ling Zhou; Dandan Huang; Xianglong Chen; Fan Zhang (Science of The Total Environment, 2024)

Sea-urchin-like covalent organic framework as solid-phase microextraction fiber coating for sensitive detection of trace pyrethroid insecticides in water - Jiajia Han; Yang Yu; Hongyu Wen; Tianning Chen; Yuemei Chen; Guosheng Chen; Junlang Qiu; Fang Zhu; Gangfeng Ouyang (Science of The Total Environment, 2024)

Regulating pathway for bacterial diversities toward improved ecological benefits of thiencarbazone-methyl·isoxaflutole application: A field experiment - Yonglu Wang; Liyun Zhang; Shumin Zhang; Shiliang Zhu; Fengsong Zhang; Guixiang Zhang; Bihua Duan; Rui Ren; Hongyu Zhang; Meng Han; Yi Xu; Yuyang Li (Journal of Environmental Management, 2024)

Isolation and characterization of 55 SNP markers in Triplophysa (Hedinichthys) yarkandensis macroptera - Qiang Li; Yeyu Chen; Hongyu Ke; Zhongmeng Zhao; Han Zhao; Jiansheng Lai; Xiaoyun Wu; Mingjiang Song; Feiyang Li; Ya Liu (Conservation Genetics Resources, 2023)

Factors regulating interaction among inorganic nitrogen and phosphorus species, plant uptake, and relevant cycling genes in a weakly alkaline soil treated with biochar and inorganic fertilizer - Hongyan Li; Rui Ren; Hongyu Zhang; Guixiang Zhang; Qiusheng He; Zhiwang Han; Shuhui Meng; Yanli Zhang; Xiaohui Zhang (Science of The Total Environment, 2023)

Trace metal exposure and risk assessment of local dominant fish species in the Beijiang River Basin of China: A 60 years' follow-up study - Zengquan Liao; Zhilin Li; Maorong Wu; Keqin Zeng; Hongyu Han; Chao Li; Ruifang Fan; Qihua Pang (Science of The Total Environment, 2023)

Pore size-tunable core-shell structured Ni-Ru Nanoparticles catalyst for the reductive amination of isosorbide diketone - Peng Liu; Hongyu Zhang; Yaping Han; Jiquan Zhao; Yuecheng Zhang (Chemical Engineering Journal, 2023)

Shrubs facilitate herbaceous communities in a desert by modifying soil properties - Lina Xie; Lei Han; Hongyu Guo; Fang Zhao; Fanglei Gao; Guogang Zhang; Chengcang Ma (Plant and Soil, 2023)

Research on the dynamic evolution and convergence of collaborative capacity of pollution control and carbon reduction: from the perspective of whole-process governance - Dongri Han; Yanxia Diao; Xinjuan Wang; Yingying Ding; Hongyu Wang (Environmental Science and Pollution Research, 2023)

Ordered porous metal oxide embedded dense carbon network design as high-performance interlayer for stable lithium-sulfur batteries - Hongyu Wang; Ce Xu; Xiaohang Du; Guihua Liu; Wenjia Han; Jingde Li (Chemical Engineering Journal, 2023)

Molecular characterization of methionine aminopeptidase1 from Eimeria tenella - Ke Xiao; Qiping Zhao; Haixia Wang; Shunhai Zhu; Hui Dong; Bing Huang; Hongyu Han (European Journal of Protistology, 2023)

Expression levels of serine proteases, their homologs, and prophenoloxidase in the Eriocheir sinensis with hepatopancreatic necrosis syndrome (HPNS) and their expression regulation by Runt - Qian Ren; Hongyu Wang; Yuqi Zhao; Zhengxiao Han; Hao Xu; Tianheng Gao; Ximei Nie; Xin Huang (Fish & Shellfish Immunology, 2023)

Optimal delta-V-based strategies in orbital pursuit-evasion games - Hongyu Han; Zhaohui Dang (Advances in Space Research, 2023)

Spatial distribution and driving factors of groundwater chemistry and pollution in an oil production region in the Northwest China - Hongyu Zhang; Xu Han; Guangcai Wang; Hairu Mao; Xianglong Chen; Ling Zhou; Dandan Huang; Fan Zhang; Xin Yan (Science of The Total Environment, 2023)

Accelerating drug repurposing for COVID-19 treatment by modeling mechanisms of action using cell image features and machine learning - Lu Han; Guangcun Shan; Bingfeng Chu; Hongyu Wang; Zhongjian Wang; Shengqiao Gao; Wenxia Zhou (Cognitive Neurodynamics, 2023)

Antiferromagnetic spintronics: towards high-density and ultrafast information technology - Peixin Qin; Xiaorong Zhou; Li Liu; Ziang Meng; Han Yan; Hongyu Chen; Xiaoning Wang; Xiaojun Wu; Zhiqi Liu (Science Bulletin, 2023)

The interaction effects between exposure to ambient PM2.5 and economic development on the settlement intention for floating population in China - Luyang Wang; Yang Zhao; Yukun Shi; Haiyun Liu; Hongyu Li; Junyan Liu; Haotian Chen; Baoshun Yang; Haifeng Shan; Shijia Yuan; Wenhui Gao; Guangcheng Wang; et al. (Environmental Science and Pollution Research, 2023)

Association between exposure to ambient PM2.5 and the health status in the mobile population from 338 cities in China - Yukun Shi; Yang Zhao; Hongyu Li; Haiyun Liu; Luyang Wang; Junyan Liu; Haotian Chen; Baoshun Yang; Haifeng Shan; Shijia Yuan; Wenhui Gao; Guangcheng Wang; et al. (Environmental Science and Pollution Research, 2023)

RETRACTED: Determining the spatial non-stationarity underlying social and natural environment in thyroid cancer in China - Xiyu Zhang; Yongqiang Lai; Xiaodan Bai; Bing Wu; Wenjing Xiang; Chenxi Zhang; Guihong Geng; Wenqing Miao; Qi Xia; Qunhong Wu; Huiying Yang; Yanjie Wang; et al. (Science of The Total Environment, 2023)

Pyrometallurgy treatment of electroplating sludge, emulsion mud and coal ash: ZnAlFeO4 spinel separation and stabilization in calcium metasilicate glass - Qin Jiabao; Qu Zhan; Chen Hongyu; Wang Zhihua; Han Qi; Zhang Yuxin; Zhang Hong; Gao Yidi; Zhang Ying; Wang Xianze; Zhu Suiyi (Journal of Environmental Management, 2023)

Sensitivity and uncertainties assessment in radiative forcing due to aerosol optical properties in diverse locations in China - Fuquan Lu; Siyu Chen; Zeyong Hu; Zhiwei Han; Khan Alam; Hongyu Luo; Hongru Bi; Junyan Chen; Xinyang Guo (Science of The Total Environment, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

A robust glacial lake outburst susceptibility assessment approach validated by GLOF event in 2020 in the Nidu Zangbo Basin, Tibetan Plateau - Dahong Zhang; Gang Zhou; Wen Li; Lei Han; Shiqiang Zhang; Xiaojun Yao; Hongyu Duan (CATENA, 2023)

Associations between short-term exposure to ambient PM2.5 and incident cases of cerebrovascular disease in Yantai, China - Junyan Liu; Maobo Wang; Yang Zhao; Haotian Chen; Haiyun Liu; Baoshun Yang; Haifeng Shan; Hongyu Li; Yukun Shi; Luyang Wang; Guangcheng Wang; Chunlei Han (Environmental Science and Pollution Research, 2022)

Development of 45 SNP markers in Triplophysa hsutschouensis based on RAD sequencing - Ya Liu; Jiansheng Lai; Zhongmeng Zhao; Hongyu Ke; Han Zhao; Yeyu Chen; Xiaoyun Wu; Qiang Li (Conservation Genetics Resources, 2022)

Integrated analysis of the miRNA and mRNA expression profiles in Leiocassis longirostris at gonadal maturation - Han Zhao; Lu Zhang; Qiang Li; Zhongmeng Zhao; Yuanliang Duan; Zhipeng Huang; Hongyu Ke; Chao Liu; Huadong Li; Lu Liu; Jun Du; Zhen Wei; et al. (Functional & Integrative Genomics, 2022)

Spontaneous neural activity in the right fusiform gyrus and putamen is associated with consummatory anhedonia in obsessive compulsive disorder - Hongyu Du; Jie Xia; Jie Fan; Feng Gao; Xiang Wang; Yan Han; Changlian Tan; Xiongzhao Zhu (Brain Imaging and Behavior, 2022)

Isolation and characterization of 45 SNP markers in Triplophysa tenuis - Ya Liu; Yeyu Chen; Jiansheng Lai; Hongyu Ke; Zhongmeng Zhao; Han Zhao; Xiaoyun Wu; Jian Zhou; Qiang Li (Conservation Genetics Resources, 2022)

MiRNA-seq analysis of spleen and head kidney tissue from aquacultured largemouth bass (Micropterus salmoides) in response to Aeromonas hydrophila infection - Jian Zhou; Han Zhao; Lu Zhang; Qiang Li; Zhipeng Huang; Zhongmeng Zhao; Hongyu Ke; Yu Xiao; Xutao Su; Qiao Liu; Song Yang; Liulan Zhao (Functional & Integrative Genomics, 2021)

Targeting Two Antigens Associated with B-ALL with CD19-CD123 Compound Car T Cell Therapy - Lulu E. Yan; Hongyu Zhang; Masayuki Wada; Liu Fang; Jia Feng; Wenli Zhang; Qi Chen; Yuanzhen Cao; Kevin G. Pinz; Kevin H. Chen; Jessica C. Petrov; Xi Chen; et al. (Stem Cell Reviews and Reports, 2020)

Photocatalytic degradation of dye by Ag/TiO2 nanoparticles prepared with different sol–gel crystallization in the presence of effluent organic matter - Hongyu Deng; Huan He; Shijie Sun; Xintong Zhu; Dongxu Zhou; Fengxia Han; Bin Huang; Xuejun Pan (Environmental Science and Pollution Research, 2019)

Integrated analysis of RNA-seq and microRNA-seq depicts miRNA–mRNA networks involved in stripe patterns of Botia superciliaris skin - Jian Zhou; Han Zhao; Lu Zhang; Can Liu; Siyuan Feng; Jideng Ma; Qiang Li; Hongyu Ke; Xinyu Wang; Lingyan Liu; Chao Liu; Xutao Su; et al. (Functional & Integrative Genomics, 2019)

Proteomics analysis of Schwann cell-derived exosomes: a novel therapeutic strategy for central nervous system injury - Zhijian Wei; Baoyou Fan; Han Ding; Yang Liu; Haoshuai Tang; Dayu Pan; Jiaxiao Shi; Pengyuan Zheng; Hongyu Shi; Heng Wu; Ang Li; Shiqing Feng (Molecular and Cellular Biochemistry, 2019)

Altered Local Field Potential Relationship Between the Parafascicular Thalamic Nucleus and Dorsal Striatum in Hemiparkinsonian Rats - Haiyan Zhang; Jing Yang; Xuenan Wang; Xiaomeng Yao; Hongyu Han; Yunfeng Gao; Hongli Chang; Tianyu Xiang; Shuang Sun; Yanan Wang; Xiusong Wang; Min Wang (Neuroscience Bulletin, 2019)

Anti-Collision Assessment and Prediction Considering Material Corrosion on an Offshore Protective Device - Ang Qiu; Xiangxi Han; Hongyu Qin; Wei Lin; Youhong Tang (Journal of Marine Science and Engineering, 2017)
Corrosion deterioration of steel can heavily degrade the performance of marine and offshore structures. A typical steel protective device, which has worked for a dozen years in a river estuary, is selected as the research object. Its current corrosion response is measured on site and its further corrosive response is predicted based on measurement data and the structure’s current state. Nonlinear finite element method is utilized to analyze the degradation of the protective device’s anti-collision performance. Meanwhile the rubber buffer effect has been investigated for its anti-collision on the protective device. A prediction method is proposed that can accurately forecast degradation of the anti-collision performance of a protective device as time progresses.

Nucleotide Diversity and Molecular Evolution of the ALK Gene in Cultivated Rice and its Wild Relatives - Ying Zhou; Hongyu Zheng; Guochao Wei; Hui Zhou; Yanni Han; Xufeng Bai; Yongzhong Xing; Yuepeng Han (Plant Molecular Biology Reporter, 2016)

The prevalence of helminth parasites in Pelophylax nigromaculatus (Anura: Ranidae) from Shanghai, China - Qifei Men; Hongyu Han; Qiping Zhao; Weili Xia; Hui Dong; Shunhai Zhu; Ziwen Wang; Cong Li; Xuelong Zhu; Bing Huang (Acta Parasitologica, 2016)
Parasites are ubiquitous members of biotic communities. To investigate the infective status of helminth parasites in

The diapycnal mixing in the upper Pacific estimated from GTSPP observations - Zeng’an Deng; Guanghao Wei; Ting Yu; Hongyu Wei; Linchong Kang; Luyao Han (Acta Oceanologica Sinica, 2016)

Determination and analysis of the dissipation and residue of cyprodinil and fludioxonil in grape and soil using a modified QuEChERS method - Wen Zhang; Hongyu Chen; Xinwei Han; Zaihui Yang; Mingming Tang; Jing Zhang; Song Zeng; Deyu Hu; Kankan Zhang (Environmental Monitoring and Assessment, 2015)

Genetic mapping of a QTL controlling leaf width and grain number in rice - Yonghang Tian; Hongyu Zhang; Peizhou Xu; Xiaoqiong Chen; Yongxiang Liao; Baolin Han; Xiangbin Chen; Xiangdong Fu; Xianjun Wu (Euphytica, 2015)

First report of Hepatozoon (Apicomplexa: Adeleorina) from king ratsnakes (Elaphe carinata) in Shanghai, with description of a new species - Hongyu Han; Youling Wu; Hui Dong; Shunhai Zhu; Liujia Li; Qiping Zhao; Di Wu; Enle Pei; Yange Wang; Bing Huang (Acta Parasitologica, 2015)
Hepatozoon species are the most common hemoparasites of snakes. In this study, Hepatozoon parasites were examined for the first time in king rat snakes (Elaphe carinata) from Shanghai, China. All 10 snakes were found to be infected with Hepatozoon gamonts. The gamonts were folded back in a hook-wise fashion for about 3 μm at one end. Parasitemia levels ranged from 4-43 infected erythrocytes per 1,000 examined. The gamonts changed the morphology of the parasitized erythrocytes. Although the gamonts showed some distinct variations in both the parasite and its nucleus, phylogenetic analysis indicated that all the E. carinata in this study formed a monophyletic group, and were distinct from all other published Hepatozoon species. A new species, Hepatozoon chinensis, was proposed based on the molecular and morphologic evidence.

Design, synthesis and 3D-QSAR study of cytotoxic flavonoid derivatives - Lili Ou; Shuang Han; Wenbo Ding; Zhe Chen; Ziqi Ye; Hongyu Yang; Goulin Zhang; Yijia Lou; Jian-Zhong Chen; Yongping Yu (Molecular Diversity, 2011)